Impresi Nazhir Terhadap Pemahaman Wakaf Uang - Rahmat Dahlan (Al-Urban: Jurnal Ekonomi Syariah dan Filantropi Islam, 2017)
This research is motivated by the low level of understanding the cash waqf, nazhir and understanding of the Law number 41 of 2004 on endowments. The purpose of this study is to analyze what factors are influencing perceptions cash waqf of nazhir. This research is a descriptive type of research-correlational (causal) by looking at the factors that have the independent variable to see is there a relationship and how much influence each independent variable to the varaiable binding. The method used to analyze the data are descriptive analysisi and logistic regression. This research done in Kebayoran baru district of South Jakarta through questionnaires from 60 respondents. The result of this study showed that perception nazhir influenced by the media access information and understanding of charitable regulation.